2023
DOI: 10.3389/fhumd.2023.1207941
|View full text |Cite
|
Sign up to set email alerts
|

Why so few expert women in the water sector? Masculinity, race, sex, and policy narratives of technology, gender and development in Nepal

Janwillem Liebrand

Abstract: To challenge the masculinity of the professional water sector, I take in this paper one of the core questions of feminist technology studies as the starting point: why are there so few expert women in technology? By means of a critical feminist reading of policy and research documents, from the 1950s onwards, focusing on Nepal's history of rural development and technology transfer, I trace the origins of expert women's limited participation in politically relevant processes of water decision making. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Furthermore, because water user groups are mostly the domains of men, women were unable to assert their new roles as decision-makers and in some cases were excluded from decision-making (van Koppen et al, 2021). Bhattarai et al (2015Bhattarai et al ( , 2021) also found that women's voices are systematically excluded from water governance in Nepal and recognize that because of the domination of men in the public sphere as local chairpersons, elected leaders, private sector members, and administrative and engineering staff and having strong networks between them, the men hardly support women in decision-making roles and silence them in some cases. Other reasons such as being not heard in the meetings among the majority of male members, time constraints to attend meetings regularly, limited budget, and adequate resource allocation for capacity-building programs for women are challenges to implementing inclusive water planning (van Koppen et al, 2021).…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…Furthermore, because water user groups are mostly the domains of men, women were unable to assert their new roles as decision-makers and in some cases were excluded from decision-making (van Koppen et al, 2021). Bhattarai et al (2015Bhattarai et al ( , 2021) also found that women's voices are systematically excluded from water governance in Nepal and recognize that because of the domination of men in the public sphere as local chairpersons, elected leaders, private sector members, and administrative and engineering staff and having strong networks between them, the men hardly support women in decision-making roles and silence them in some cases. Other reasons such as being not heard in the meetings among the majority of male members, time constraints to attend meetings regularly, limited budget, and adequate resource allocation for capacity-building programs for women are challenges to implementing inclusive water planning (van Koppen et al, 2021).…”
Section: Conclusion and Limitationsmentioning
confidence: 99%